A Facile Approach for Fabricating Dual‐Function Membrane: Simultaneously Removing Oil from Water and Adsorbing Water‐Soluble Proteins. Issue 16 (6th June 2016) - Zhang, Qingdong; Cao, Yingze; Liu, Na; Zhang, Weifeng; Chen, Yuning; Lin, Xin; Tao, Lei; Wei, Yen; Feng, Lin
Abstract : A novel dual‐function membrane is developed that can simultaneously remove oil from water and adsorb water‐soluble proteins by combining mussel‐inspired chemistry and 1‐(3‐Dimethylaminopropyl)‐3‐ethylcarbodiimide hydrochloride/N‐Hydroxysuccinimide (EDC/NHS) activated amide reaction (EDC/NHS coupling reaction). This study provides a new prospect to introduce multiple molecules on the polydopamine/polyethylenepolyamine film to achieve various functional oil/water separation materials.